Python for Teenagers Learn to Program Like a Superhero! - Payne, James R (Berkeley, CA Apress : Imprint: Apress, 2019)
Discover everything you need to learn Python programming, with fun examples along the way. This book gives you ideas for how to turn your love of programming into a job you'll love. Start with the basics and before you know it, you'll be building your own web sites, doing white-hat hacking, finding code bugs and errors, and creating games, including using Python to roll characters for RPGs. Every chapter is relaxed
1
Keywords: COMPUTERS / Programming Languages / Python; Python (Langage de programmation)